Venecia, Josep Pla, Nápoles: diversas ciudades, pasos distintos - Ribera Llopis, Juan M. (Revista de Filología Románica, 2006)
This article studies some pages from the Cartes d’Itàlia (1954) by Josep Pla dedicated to Venice and Naples. After paying attention to the bases of the author’s writings, and admitting for those two cities a double kind of urban space – Circular city or City-Island and Linear City or City-Shore, the journey and the steps of the traveller, in that double urban space, should be different, as long as it happens in the writings at his service.